Pelindungan Pekerja Migran Perempuan di Sektor Domestik dalam Perspektif Feminist Legal Theory - Alfin Dwi Novemyanto; Rismawati Nur; Muhammad Rosyid Ridlo (Fakultas Hukum Universitas Islam Indonesia, 2025)
Women migrant workers in the domestic sector are the most vulnerable group in the labor structure, mainly due to the lack of formal recognition in national law and weak protection of their basic rights. In Indonesia, despite their significant economic contribution, existing regulations are still partial and do not address the substance of gender-based justice. This article analyzes legal protection for women migrant workers through a feminist legal theory approach to uncover structural inequalities and patriarchal biases in the labor law system. The research employs a normative method with a conceptual and legislative approach, as well as a systematic analysis of primary and secondary data. The results of the study show that domestic workers are still not recognized as subjects of formal employment relationships, leaving them trapped in private workspaces with minimal state oversight. A feminist approach is used to evaluate this injustice and recommend transformative legal reforms, including the ratification of ILO Convention No. 189 and the harmonization of national regulations based on gender justice to provide substantial and inclusive justice for women migrant workers.